2003
DOI: 10.1097/01.lab.0000048719.53282.00
|View full text |Cite
|
Sign up to set email alerts
|

The CXC Chemokine GCP-2/CXCL6 Is Predominantly Induced in Mesenchymal Cells by Interleukin-1β and Is Down-Regulated by Interferon-γ: Comparison with Interleukin-8/CXCL8

Abstract: SUMMARY:Human granulocyte chemotactic protein-2 (GCP-2)/CXCL6 is a CXC chemokine that functionally uses both of the IL-8/CXCL8 receptors to chemoattract neutrophils but that is structurally most related to epithelial cell-derived neutrophil attractant-78 (ENA-78)/CXCL5. This study provides the first evidence that GCP-2 protein is, compared with IL-8, weakly produced by some sarcoma, but less by carcinoma cells, and is tightly regulated in normal mesenchymal cells. IL-1␤ was the predominant GCP-2 inducer in fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 53 publications
9
62
1
Order By: Relevance
“…Next to lymphocyte recruitment, IFN-␥ also affects inflammatory neutrophil recruitment. Production of neutrophil attracting and activating chemokine granulocyte chemotactic protein-2 by stimulated human fibroblasts and murine macrophage-derived KC and MIP-2 are down-regulated by IFN-␥ (43,44). In vitro studies using RA fibroblasts demonstrated IFN-␥ to significantly reduce neutrophil-activating chemokine CXCL8 generation induced by IL-1␤ or TNF-␣, but in contrast increase CCL2 production (45).…”
Section: Discussionmentioning
confidence: 99%
“…Next to lymphocyte recruitment, IFN-␥ also affects inflammatory neutrophil recruitment. Production of neutrophil attracting and activating chemokine granulocyte chemotactic protein-2 by stimulated human fibroblasts and murine macrophage-derived KC and MIP-2 are down-regulated by IFN-␥ (43,44). In vitro studies using RA fibroblasts demonstrated IFN-␥ to significantly reduce neutrophil-activating chemokine CXCL8 generation induced by IL-1␤ or TNF-␣, but in contrast increase CCL2 production (45).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of IL-8 in the culture supernatant of the infected cells was determined by enzyme-linked immunosorbent assay (ELISA). For IL-8 detection, a polyclonal goat anti-human IL-8 antibody for coating (61) and a monoclonal mouse anti-human IL-8 antibody (R&D Systems, Abingdon, United Kingdom) were used as described previously (68). As a positive control for IL-8 production, cells were stimulated for 24 h with 5 g/l lipopolysaccharide (LPS) (Escherichia coli O111:B4) (Difco Laboratories, Detroit, Mich.).…”
Section: Methodsmentioning
confidence: 99%
“…Regulation of granulocyte chemotactic protein-2 secretion by IL-1b IL-1b has been shown to be the predominant inducer of GCP-2 in non-tumour cells such as mesenchymal cells (Wuyts et al, 2003) and endometrial stromal cells (Mine et al, 2003). To assess whether IL-1b induces GCP-2 in SCLC cell lines, the high-GCP-2-producing H345 and H711 cells were treated by rIL-1b at a final concentration of 0.1 or 1 ng ml À1 for 24 h ( Figure 3A).…”
Section: Constitutive Expression Of Granulocyte Chemotactic Protein-2mentioning
confidence: 99%